Response of sedimentary processes to cyanobacteria loading - Mindaugas Zilius (Journal of Limnology, 2015)
Sedimentation of pelagic cyanobacteria in dystrophic freshwater and oligohaline lagoons results in large inputs of labile organic matter (OM) to the benthos. We used an experimental approach to study the short-term impact of such phenomena on the benthic microbial community metabolism and on the nitrogen (N) fluxes across the sediment-water interface. We hypothesized an increase of respiratory activity, including N loss via denitrification and its recycling to the water column. Our results show that the incorporation within sediments of the settled bloom increases benthic bacterial activities. This is coupled to large DON and NH4+ effluxes, and to a comparatively smaller increase of N2 production, while no significant effects were detected for the benthic fluxes of NOx-. We constructed flow schemes for N compounds, which show that while denitrification was significantly stimulated by amending cyanobacterial biomass to the sediments, it represented less than 1% of total OM mineralization. Interestingly, we observed that total released nitrogen (DIN+DON+N2 efflux) was dominated by DON, which contributed 75–80 % of the net N efflux, suggesting incomplete mineralization of OM. With the measured total N mobilization rate of about 15 mmol N m-2 d-1 it would take more than 4 months to regenerate the total organic N input to sediments (2031 mmol N m-2), which represents the post-bloom deposited particulate organic N. These results suggest limited losses to the atmosphere and slow diffusive recycling of N buried into sediments, mostly as DON. Such regenerated N may eventually be flushed to the open sea or sustain pelagic blooms within the estuarine environment, including cyanobacteria, with a negative feedback for further import of atmospheric nitrogen via N-fixation.